Kajian Perbandingan Nilai Ambang Batas dan Klasifikasi Bahan Kimia yang Bersifat Karsinogen Terhadap Manusia pada Standar Indonesia dengan TLV ACGIH - Ferananda, Martina Caisar (Komunitas Menulis dan Meneliti (Kolibi), 2023)
The study compared NAB concentrations and classification of carcinogenic chemicals on three standards in Indonesia with ACGIH TLV 2023. NAB has been regulated by Indonesia to prevent the adverse impacts of the use of chemicals and regulate exposure at work, with the aim ofining a weighted average rate or intensity of time that can be accepted by the workforce without causing illness or health disorders. Differences in notation in the classification of carcinogens for the same product can lead to inconsistent protection and heavy regulatory burden for companies. Chemical exposure in the workplace can have adverse effects, carcinogenic chemicals will cause cancer. The International Labour Organization (ILO) estimates that millions of workers die from accidents and illnesses at work each year. This research contributes to continuous improvement to protect workers at work through changes in work exposure limits. ASEAN initiatives in the control of hazardous chemicals such as pesticides are underway, but differences on NAB and the classification of carcinogens in Indonesia vary. This study provides a comparison and analysis of the NAB carcinogenic chemicals in three tandar that are valid in Indonesia with the ACGIH TLV 2023. The results of this study are expected to inform measures to reduce the risk of exposure to chemicals at work and to serve as a reference for the country in relation to NAB concentration values and notations that are not updated and there are classifications and categories of human carcinogenic chemical which are not listed in the applicable standards